Mediating role of resilience in the relationship between mindfulness and mental health - Nishit Kumar Sinha (Frontiers in Psychology, 2025)
Past research has established the beneficial effects of mindfulness on mental health. The present study attempts to extend the previous literature by examining the potential mediating role of resilience between mindfulness and mental health relationships. A survey questionnaire comprising the Cognitive and Affective Mindfulness Scale-Revised (CAMS-R), Wagnild and Young Brief Resilience scale, and Mental Health Continuum–Short Form (MHC-SF) was administered to 431 respondents from India. Confirmatory factor analysis confirmed the tripartite structure of MHC–SF, developed by to facilitate mental health assessment (including its three components: emotional, psychological, and social), in the Indian context. The study outcomes revealed that mindfulness was significantly associated with mental health (β = 0.472, p < 0.001) and its three dimensions: emotional (β = 0.405, p < 0.001), psychological (β = 0.480, p < 0.001), and social well-being (β = 0.296, p < 0.001). Resilience mediated the relationship between mindfulness and mental health, and its dimensions. The study findings provide information regarding the previously unknown resilience process through which mindfulness exerts its beneficial effects on mental health.